Marriage conditionally in the light of the Code of Canon Law of 1983 and the Code of Canons of the Eastern Churches of 1990 - GOŁĘBIOWSKA, ANNA (Prawo Kanoniczne, 2012)
The issue of marriages conditionally institutions is complex. Marriage is provided by the doctrine of the Catholic Church has always been difficult and causing divergence of views in this area. Therefore, the expression of marital consent condition can result in the nullity of marriage, and therefore is considered to be defects in consent. Code of Canon Law of 1983 addicted validity of marriage on the type of condition. Code of Canons of the Eastern Churches of 1990 denied the validity of any marriage contained the condition.